Prevalence of anaplasmosis on dairy farms in the European region (Thrace) of Türkiye: A retrospective study on the effectiveness of two different treatment protocols - Aydin, Levent; Kacar, Yigit; Aktas, Munir; Batmaz, Hasan (Veterinarni A Farmaceuticka Univerzita Brno, 2024)
This study was conducted in 2015-2022 to determine the status of anaplasmosis in breeding dairy cattle farms imported from abroad in the Thrace region of T & uuml;rkiye. To investigate the presence of Anaplasma spp. blood samples with EDTA were taken from animals aged two years and older between 05.00 am and 10.00 am. Then a blood smear was prepared with the Diff-Quick staining method and examined under the light microscope at a x 100 magnification with immersion in oil. In addition, 40 randomly selected positive blood samples were analysed by the Nested PCR method. A total of 3,051 blood samples were examined by the Diff-Quick staining method. One hundred eleven of 966 samples (11.49%) in K & imath;rklareli province and 297 of 2,085 (14.24%) samples in Tekirdag province were positive. As a result of nested PCR on 40 randomly selected positive samples from both provinces, the rates of A. marginale, A. centrale, and mixed infection (A. marginale and A. centrale) were determined as 34.5%, 4.0%, and 61.5% respectively. Of the 140 positive cattle, 70 were treated with oxytetracycline (Group 1), and the other 70 ones were treated with oxytetracycline-imidocarb combination (Group 2) twice with two month intervals for comparison. At the third examination, the rate of latent infection in the group treated with oxytetracycline-imidocarb combination was lower than in the group treated with oxytetracycline alone, but the difference was not significant (P > 0.05). As a result, it was revealed that anaplasmosis is a common disease in cattle in the Thrace region, and the combination of oxytetracycline and imidocarb was shown to be more successful than using oxytetracycline alone in reducing latent infected anaplasmosis cases.
Keywords: Cattle; anaplasma; imidocarb; oxytetracycline